The motif of crime and punishment in the works of Ivan Bunin (Eurasian Journal of Philology Science and Education, 2018)
The article deals with actual problems of study of some facets of creativity of the Russian writer of the twentieth century, Ivan Bunin, whose work is closely related to the ideological and artistic principles and traditions of the realistic literature of the last century. The article deals with actual problems of study of some facets of creativity of the Russian writer of the twentieth century, Ivan Bunin, whose work is closely related to the ideological and artistic principles and traditions of the realistic literature of the last century. The article highlighted the idea that the writer used a lot of motives, but the main motive was crime and punishment human Life. The author considers the work of the writer works, which presented only some one from experiencing in his inner world «truths». This really is the concealment of the crime, for which one should expect punishment. The article proves the idea that Bunin in most of the works remained loyal to the basic motives of his work: from the humanist position rebels against crimes in the society and requires just punishment.